The Influence Literacy, Income and Financial Attitude on Financial Management Behavior - Nataliana Bebasari; Parulian Parulian (Daengku: Journal of Humanities and Social Sciences Innovation, 2024)
The problem in this research is the consumptive behavior carried out by the community or the lack of good financial management behavior. This is supported by the rapid development of technology that has an impact on people's lifestyles. This study aims to examine the effect of financial literacy on financial management behavior. This study aims to examine the effect of income on financial management behavior. This study aims to examine the effect of financial attitude on financial management behavior. The sampling method used is a quantitative method by collecting surveys or questionnaires. The sample in the study was 100 students of the Faculty of Economics, Business and Social Sciences at Pelita Bangsa University. The author uses a Likert scale in measuring variables with simple random sampling technique. The data analysis used was multiple linear regression analysis with the help of SPSS version 23. The results of this study indicate that Financial Literacy influences Financial Management Behavior, Income influences Financial Management Behavior, Financial Attitude influences Financial Management Behavior.